Trigonometric Approximation of Functions in Weighted $\boldsymbol{L^{p}}$ Spaces - Guven, Ali (Sarajevo Journal of Mathematics, 2024)
The approximation properties of means of trigonometric Fourier series in weighted $L^{p}$ spaces $ \left( 1<p<∞ \right) $ with Muckenhoupt weights are investigated. 2000 Mathematics Subject Classification. 41A25, 42A10